(untitled) (Hekima Review, 2015)
In recent decades, republican political theory has undergone a striking resurgence, enriching at the same time contemporary debates around democracy and social justice. The idea of liberty as non-domination against private domination (dominium) and public domination (imperium) as developed in this article is one face of these resurgent questions that address the challenges entailed in constructing a broadly egalitarian theory of social justice. Inspired by Philip Pettit’s work on Republicanism, this article intends to present non-domination as a root of political freedom that gives the provision of a democratic constitution, in such a way that it might inspire eminently practical ways through which “positive freedom” can be increased by minimizing asymmetries of power at work within organizational life. In so doing, such a reflection addresses a major aspect of democracy whose aim is to promote more political freedom opposing the human drive to dominate, facing the sovereignty or will-power, and establishing policies that guaranty freedom, equality, and justice.